Investigating the impact of cross-shelf transport and local retention in the Black Sea Rim Current system on small pelagic fishes - Fach, Bettina A.; Cagdas, Bulut; Arkin, Sinan S.; Salihoglu, Baris; Tezcan, Devrim (Frontiers in Marine Science, 2024)
Advection of pelagic fish larvae through ocean currents is a source of dispersal that is known to structure marine populations by directly impacting population success and persistence. To be able to understand fish population dynamics and manage existing fisheries it is therefore of importance to assess the extent of exchange between populations and determine the factors that drive it, which is still a challenge in fisheries research today. In this study, the output of a high-resolution basinscale circulation model is used to calculate the dispersal probability from spawning areas and the remaining Black Sea for a range of commercially important fish such as anchovy, sprat, turbot, red mullet, and bluefish under different environmental conditions. The common trait of many commercially important species in the Black Sea is that they have pelagic larval stages of different time scales which are simulated by tracking virtual drifters in the simulated surface circulation of the Black Sea.Simulation results show that the dynamic current structure of the Black Sea causes low local retention of larvae. During spring and summer lower offshore transport and higher local retention is observed than in fall and winter, which is directly related to the Rim Current strength. The lowest offshore transport is observed on the northern northwestern shelf, the main spawning area for pelagic fish with still 24-32% of larvae transported offshore. Simulations show that pelagic fish species such as anchovy and sprat adopted different reproductive strategies through their speciesspecific traits. For the summer spawning species anchovy, timing, and location of spawning together with its short pelagic larval stage is shown to enhance retention on the northwestern shelf. Sprat with its long pelagic larval stage and winter spawning is more adapted to high offshore transport, making it unlikely that sprat is recruited to the same area as where it is spawned. This modeling framework provides a basis for investigating recruitment variability of pelagic fish species in the Black Sea specifically considering the impact of climate variability and provides a useful guide to the potential connectivity of marine populations or the spread of invasive pests in the Black Sea.